Heavy-oil recovery by combined geothermal energy and cosolvent/water flooding. (1st August 2021) - Wang, Chen; Liu, Yueliang; Du, Yifan; Gao, Yuan; Sun, Yuanxiu
Abstract: Water flooding has been accepted as the first-hand strategy for oil recovery as well as for unconventional oil reservoir development. However, a large amount of heavy oil is generally left over after a long period of water flooding due to the figuring effect. In this work, geothermal energy and cosolvents are proposed to assist water flooding for heavy oil recovery. The influences of cosolvents and temperature on the viscosity of heavy oil is first investigated. NMR technique is then applied to investigate the performance of geothermal energy and cosolvents for enhancing heavy oil exploration. Results show that the addition of methanol and ethanol significantly decreases the viscosity of heavy oil as much as 93.95%; in addition, viscosity of heavy oil is reduced as temperature increases. Compared to water flooding, geothermal assisted water flooding recovers 28.3% more oil from the heavy-oil saturated core samples by reducing the viscosity of in-situ heavy oil. The addition of methanol and ethanol into the injected water enables the injected water to enter the smaller pores and recover more heavy oil from such pores. Thereby, the geothermal methanol- and ethanol-assisted water flooding show better performance for enhancing heavy oil exploitation than pure water flooding. Highlights: Addition of alcohol significantly reduces the viscosity of heavy oil. Alcohol enables water flooding to enhance heavy oil recovery from the smaller pores. Combination of geothermal energy recovers more heavy oil than pure water flooding.